PENGEMBANGA MEDIA KOMIK DIGITAL BERBASIS PHOTOSHOP TEMA PANAS DAN PERPINDAHANNYA SUBTEMA SUHU DAN KALOR - Ristie Maulina Pratiwi Sunardi; Fitri Siti Sundari; Dendy Saeful Zen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Learning media is one of the strategies that can be used teacher in helpimh the learning process in the class, the lack of us of learning media that the delivery of learning materials greatly affects students' ability to understand learning materials, especially in science learning. The research metod in this studi is the Research and Development (R&D) with the ADDIE delevopment model namely Analysis, Design, Development, Implementation, and Evaluation. This ADDIE model is used to help develop photoshop-based digital comic media which can be used as an alternative in helping the learning process. Based on the results of the validation of media experts, they got a validity score of 80% with very valid criteria, the validation results of linguists got a validity score of 76.36% with valid criteria, and the results of material expert validation got a 95% validity score with very valid criteria. This photoshop-based digital comic media is very valid and can be tested on teachers and students at school. Based on the results of the test through the teacher's response questionnaire, the response score was 86.66% and the test on the student's response got a score of 92.8% with a very good category. Based on the results of the two trials, it can be concluded that this photoshop-based digital comic media is valid and very well used in science learning.